A Localized Aldara (5% Imiquimod)–Induced Psoriasiform Dermatitis Model in Mice Using Finn Chambers. Issue 1 (13th August 2020) - Horváth, Szabina; Kemény, Ágnes; Pintér, Erika; Gyulai, Rolland
Abstract: The expanding number of research studies utilizing the imiquimod‐induced psoriasiform dermatitis model attests to the usefulness of this procedure. Advantages of this model include rapid development of the skin response and cost‐effectiveness. A major limitation is that application of imiquimod cream over large areas of skin, as well as licking and ingestion of the cream, may lead to severe systemic inflammation, which can cause a general decline in health, splenomegaly, and death. In this protocol, Finn chambers are used to localize the imiquimod cream to a small area of the skin. This results in production of severe and reproducible psoriatic skin reactions with significantly less imiquimod, greatly reducing the possibility of untoward systemic effects. Moreover, having psoriasiform and control skin areas on the same mice decreases inter‐animal differences. The protocol can be readily adapted for other skin disease models involving topical application of test agents. This article also details functional measurements performed during assays, including skin thickness, blood perfusion, semiquantitative histopathological evaluation, determination of scaling score to monitor psoriatic symptoms, and collection of spleen and body weight data to identify systemic effects. © 2020 The Authors. Basic Protocol : Use of Finn chambers to induce psoriasiform skin reactions with imiquimod Support Protocol 1 : Measurement of double‐fold dorsal skin thickness Support Protocol 2 : Measurement of blood perfusion Support Protocol 3 : Determination of scaling score Support Protocol 4 : Semiquantitative histopathological scoring Support Protocol 5 : Assessment of systemic side effects in response to imiquimod application